THE EFFECT OF WORK FROM HOME, WORK ENVIRONMENT AND QUALITY OF WORK LIFE ON THE WORK PRODUCTIVITY OF LECTURERS DURING THE POST-COVID-19 RECOVERY PERIOD - Rozalinda Rozalinda; Helmalia Helmalia; Era Junita (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2021)
This study aims to examine the effect of work from home, work environment and quality of work life on the work productivity of lecturers during the post-covid-19 recovery period. This is a field research by using quantitative approach. The population in this study was the lecturers of FEBI UIN Imam Bonjol Padang using a total sampling technique. Data processing in this study was through SPSS using primary data. The data was analyzed by using multiple linear regression model. The results of this study indicated that work from home had a positive and significant effect on the work productivity of lecturers. The work environment had a negative and insignificant effect on the work productivity of lecturers. Quality of work life had a negative and insignificant effect on the work productivity of lecturers. Work from home, work environment, and quality of work life simultaneously have a significant effect on the work productivity of lecturers during the post-covid 19 recovery period. By implementing hybrid strategies and methods, the productivity level of lecturers can continue to be increased. Then, the provision of adequate infrastructure as well as effective and efficient time management needs to be done in order to avoid technostress.